Conversor duplo Forward PWM a duas chaves principais e duas chaves auxiliares com comutação suave - Borges, Arthur Jardim Nogueira (2006)
Converting a constant voltage in another constant voltage is necessary in many technological applications, starting from charging a cell phone battery to feed a DC motor in industrial plants. This work presents one more way to convert a Constant voltage based on a new circuit topology. This topology has its embryo in the simplest step-down configuration, the Buck converter. This converter has evolved to the Forward converter that is essentially a Buck converter in which load and source are isolated by a transformer. It s presented an evolution of the Forward converter making use of four windings at the transformer and of nondissipative commutation through resonant circuits. The resonance is started by an auxiliary switch which allows controlling the output voltage by pulse width modulation that has as benefit the use of a constant switching frequency.